Low-thermal-conductivity nitrogen-doped graphene aerogels for thermal insulation. Issue 12 (25th January 2016) - Yue, Chenwu; Feng, Jian; Feng, Junzong; Jiang, Yonggang
Abstract : N-doped graphene aerogels with low thermal conductivity were prepared for the first time. Abstract : Aerogels such as SiO2 aerogels, Al2 O3 aerogels and carbon aerogels have been widely used in thermal insulation. However, graphene aerogels (or reduced graphene oxide aerogels), which have similar structures, have never been used in this field. In this paper, the concept of suppressing the thermal conductivities of graphene aerogels by introducing defects or doping atoms in graphene was introduced. Nitrogen-doped (N-doped) graphene aerogels with low thermal conductivity were prepared with para phenylene diamine as a bridging and doping agent by CO2 supercritical drying. With the introduction of doping atoms and the bridging agent, the solid thermal conductivity is depressed. Also, with CO2 supercritical drying, the pore size is reduced, and the gaseous thermal conductivity is suppressed. The lowest thermal conductivity of N-doped graphene aerogels is 0.023 W (m −1 K −1 ), which is nearly 1/2 of the lowest reported value and even lower than that of static air. Meanwhile, the thermal insulation mechanisms were also studied. The low thermal conductivity and low bulk density make N-doped graphene aerogels a potentially useful thermal insulation material that may significantly lighten thermal insulation systems.